Overview of the Mental Health Conditions of Active Students at University X in Jakarta - Marceline, Linda; Sokang, Yasinta Astin (Psyche 165 Journal, 2025)
Students are a vulnerable group experiencing mental health problems due to challenges and pressures during the learning process in higher education. Various studies indicate the presence of mental health disorders experienced by students. However, there are not many studies that specifically discuss the mental health conditions of students in Jakarta covering various study programs and year classes. Thus, this study aims to determine the description of the mental health conditions of active students at University X Jakarta. This study is a quantitative study with a descriptive method. Data collection for this study used a survey, with a questionnaire instrument. The data collection instrument for this study used the Self-Reporting Questionnaire 29 (SRQ 29). The sampling of this study used a purposive sampling method, with sample criteria being active students at University X. The results of this study found that active students at University X experienced psychological symptoms that lead to four types of disorders, namely post-traumatic stress disorder (PTSD) by 55.3%, emotional mental disorders (GME) by 43%, psychotic disorders by 16%, and addiction disorders by 4.6%. Overall, as many as 260 students (79.7%) were indicated as having mental health disorders. This study also found that students can exhibit more than one disorder at a time. High rates of mental health disorders were found in the Psychology study program, graduating in 2021 and 2024. This research has implications for implementing regular mental health screenings so universities can continuously monitor students' mental health and initiate early intervention.